The Effect of Hard Skills and Soft Skills on Employee Performance - R. Rani; Suparni Sampetan; S. Sukri (Manunggal Halim Jaya, 2026)
This study aims to examine the influence of Hard skills and Soft skills on Employee Performance, as well as to provide a clear picture of the relationship between the two and their contribution to improving employee performance. This study uses a quantitative approach with a descriptive research type, which was conducted at the company PT Perumda Tirta Mangkaluku Palopo City. The population in this study was 316 employees and the sample used was 76 respondents who were selected randomly. Data collected using questionnaires and analyzed using validity and reliability tests, classical assumption tests, and hypothesis testing. The results of the study indicate that Hard skills and soft skills have a significant effect on employee performance, both partially and simultaneously. The implication of this study is that companies need to improve the development of Hard skills and soft skills of employees in a balanced manner to improve employee performance. This study also contributes to the development of a human resource model that emphasizes the balance of Hard skill and soft skill competencies in forming a productive, adaptive, and competitive workforce.